Experimental study of the autoignition properties of n-butanol–diesel fuel blends at various ambient gas temperatures. (1st January 2019) - Kuszewski, Hubert
Highlights: Ignition and combustion delay period for n-butanol–diesel fuel blends was measured. Tests of autoignition properties were conducted for different ambient gas temperatures. Derived cetane numbers for fuel samples were determined. During investigation, the constant volume combustion chamber was used. Abstract: One of the methods of reducing the nitrogen oxides and smoke emissions from the exhaust gas of diesel engines is to use fuels containing an increased fraction of oxygen compounds. This can be achieved by adding oxygen compounds, in the form of alcohols, to a standard diesel fuel including, for example, ethanol, methanol and n-butanol. Due to a number of advantages over ethanol and methanol, n-butanol is of particular interest. Particularly important, in regard to the functioning of the diesel engine, is to determine, among others things, the autoignition properties of diesel fuel to which such alcohol has been added. In this study, the autoignition properties of blends of standard diesel fuel and n-butanol were tested, with n-butanol volume fractions of up to 25%. The tests were carried out in a constant volume combustion chamber, which allowed for the determination of the effect of the ambient gas temperature (in the range 550 °C–650 °C) on the ignition and combustion delay periods of the tested fuels. The average and maximum pressure rise rates, as well as the maximum pressure rise values in the combustion chamber, were also analysed. Investigations of the autoignition properties were supplemented with the derived cetane number and the Lower and Higher Heating Values of the tested blends. This study has demonstrated a number of properties relating to such mixtures, including that with an increase in the n-butanol volume fraction in the n-butanol–diesel fuel blend, the periods of ignition and combustion delay increase, and that an increase in the ambient gas temperature into which the fuel is injected shortens these periods to a varying extent. It has also been shown that in the range of 5%–25% n-butanol volume fraction, for each increase in n-butanol fraction of 5%, the derived cetane number of the n-butanol–diesel fuel blend reduces by, on average, 2.9 units.